2018
DOI: 10.1186/s12944-018-0682-z
|View full text |Cite
|
Sign up to set email alerts
|

Policosanol composition, antioxidant and anti-arthritic activities of milk thistle (Silybium marianum L.) oil at different seed maturity stages

Abstract: BackgroundSeveral anti-arthritic drugs and synthetic antioxidants have wide pharmaceutical uses and are often associated with various side effects on the human health. Dietary seed oils and their minor components like policosanol may offer an effective alternative treatment for arthritic and oxidative-stress related diseases. The biological effects of seed oils were affected by different parameters such as the stage of seed maturity. Hence, this study seeks to determine the policosanol content, antioxidant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 37 publications
3
27
0
1
Order By: Relevance
“…Greater SOD and GPx levels, as seen in the OCT group, would be beneficial, as SOD eliminates harmful free oxygen radicals 25 and GPx reduces the damaging effects of lipid peroxidation. 26 These improvements are believed to be due to the antioxidant effects of octacosanol, as one study found strong antiradical properties of octacosanol (96.42% and 90.35% antiradical activity from the DPPH and ABTS radical scavenging assays, respectively), 27 while another study demonstrated the ability of octacosanol to decrease oxidative stress markers in an animal model. 28 This form of sports training may also lead to an increase in systemic inflammation, as inflammatory markers, such as C-reactive protein and interleukin-6, have been shown to be correlated with elevated lipid profiles and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Greater SOD and GPx levels, as seen in the OCT group, would be beneficial, as SOD eliminates harmful free oxygen radicals 25 and GPx reduces the damaging effects of lipid peroxidation. 26 These improvements are believed to be due to the antioxidant effects of octacosanol, as one study found strong antiradical properties of octacosanol (96.42% and 90.35% antiradical activity from the DPPH and ABTS radical scavenging assays, respectively), 27 while another study demonstrated the ability of octacosanol to decrease oxidative stress markers in an animal model. 28 This form of sports training may also lead to an increase in systemic inflammation, as inflammatory markers, such as C-reactive protein and interleukin-6, have been shown to be correlated with elevated lipid profiles and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Argan oil, which contains tocopherols, polyphenols, squalene, triterpene alcohols, and sterols, has been used in skin care products and the treatment of skin infections [20]. A previous study further showed the protective effects of vitamin E on keratinocyte damage in a cell culture experiment [21], while Harrabi et al [22] reported that the policosanol level in seed oils may contribute to their antioxidant. Phytosterols have also shown positive effects on skin barrier recovery [23].…”
Section: Phytochemical Contents Of Usmmentioning
confidence: 99%
“…S. marianum can therefore also be used in human nutrition [ 12 ]. A recent study demonstrated the antatritic and antioxidant effects of milk thistle oil proving the potential to utilize these effects in the food and pharmaceuctical industries [ 13 ].…”
Section: Introductionmentioning
confidence: 99%